Analisis Kebebasan Pers dalam Novel Laut Bercerita Karya Leila S. Chudori - Niken Ayu Cahyani; Ahmad Harun Yahya; Muslimin . (CV. ITTC INDONESIA, 2026)
This research is based on the fact that journalists' editorial statements in novels are often used by the press (or journalists/writers with press backgrounds) to describe the state of the press world for several important reasons, namely greater freedom of expression. Leila S. Chudori's novel Laut Bercerita tells the dramatic story of student activists during the New Order era in Indonesia. The purpose of this research is to examine press freedom in Leila S. Chudori's novel Laut Bercerita. The title of the paper is